Hydrometallurgical processing of molybdenum middlings from Shatyrkul-Zhaysan cluster ore (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
The results of physical-chemical studies with determination of the material composition of the sample and studies on nitric acid leaching of molybdenum, extraction processing of solutions from molybdenum middlings from the ore of the Shatyrkul-Zhaysan cluster (Republic of Kazakhstan) are presented. Molybdenum intermediate product obtained after the selective flotation of copper-molybdenum concentrate was used in the experiment with a yield of 0.07% with a molybdenum content of 22.23% with an extraction of 74.91%. Studying of ore minerals was carried out in reflected light with the use of a microscope OLYMPUS BX53. During the mineralographic study of the molybdenum intermediate product, an approximate ratio of ore and non-ore minerals was visually established as 80:20%. The process of the intermediate product processing was carried out using one-stage counter-current leaching at atmospheric pressure to reduce the consumption of nitric acid and, consequently, to reduce the residual acidity of the productive solutions, directed to the extraction of valuable components through extraction/re-extraction solutions and precipitation of calcium molybdate. In the process of leaching, the reduction of the residual acidity of the pregnant solution (from 2.3 to 0.89 g-eq/l) due to two-stage leaching allows to considerably increase the extraction/re-extraction stage molybdenum recovery from 58.46% to 94.28%.
Keywords: leaching; nitric acid; extracting; environmental friendliness; minerals.